Typical farming Country, Taabinga, North Coast Line, S.Q. (A.J. Cumming, Govt. Printer)
Australia Pavilion Postcard. Note On verso: Queensland produced 242, 837 tons of raw sugar in 1913, valued at 3,520,000 ($17,072,000.00)